"Apollon Maikov. About the Holy Blessed Grand Duke Alexander Yaroslavich Nevsky and the Tatar Invasion." Text Preparation, Introductory Article and Comments by Olga V. Sedelnikova, Anastasia V. Baldova, Irina S. Andrianova - Olga V. Sedelnikova; Anastasia V. Baldova; Irina S. Andrianova (Достоевский и мировая культура: Филологический журнал)
This publication introduces readers for the first time to the final typeset draft of A.N. Maikov’s story “About the Holy Blessed Grand Duke Alexander Yaroslavich Nevsky and the Tatar Invasion,” which, judging by the earliest of the surviving plans for the unfinished cycle Tales from Russian History, was intended to open the work. In a letter dated April 12, 1869, to Fyodor Dostoevsky, the poet announced the completion of this story. However, the first story published in the cycle (in the fifth issue of the magazine “Zarya” for 1869) was the subsequent planned piece, “About the Holy Moscow Metropolitans Peter and Alexy and about the Glorious Slaughter of Mamai.” During research in the Maikov archive, a set of manuscripts was discovered in the Manuscript Department of the Institute of Russian Literature RAS, including both preparatory materials and the typeset manuscript of the story about Alexander Nevsky. This evidence points to the existence of a final version of the text ready for publication. The reason for Maikov’s decision not to publish the story—despite its completion and his mention of it to Dostoevsky—remains unclear. Perhaps the poet, known for his exactingness towards himself, intended to make further revision and then, due to work obligations and other matters, postponed his efforts. He returned to contemplating this idea in the 1880s but never published it. An analysis of the manuscript’s content and artistic features reveals that Maikov abandoned the biographical principle in presenting the material, which he noted in one of the preparatory documents. The story’s title reflects this, linking Alexander’s image to the catastrophe that befell Russia during his reign and the pivotal challenges he faced. This principle is also implemented in the structure of the plot, a significant part of which describes Batu’s troops capturing fragmented Russian lands. Against this backdrop, Maikov portrays Alexander Nevsky as a wise diplomat and subtle politician who understood how to save Russia from destruction at a time when Europe and Asia simultaneously turned against it. In Maikov’s conception, Alexander Nevsky emerges as the first Russian ruler who managed to forge the only viable path at this critical historical juncture, allowing him to preserve his native land and the spiritual values of the Russian people.